2009
DOI: 10.1111/j.1468-1331.2009.02623.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of ALS in Padova district, Italy, from 1992 to 2005

Abstract: This study confirmed an ALS incidence increase over the last 25 years in the Padova district. The increase in incidence may be partially explained by the ageing of the general population rather than by an improved diagnostic assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…With respect to age, the majority of studies report a greater number of patients in the 50-70 year agegroup, frequency ranging from 53.4% [18] to 68.1% [19]. The present study in which 148 patients (65.2%) were over 50 years of age is in agreement with those reports.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…With respect to age, the majority of studies report a greater number of patients in the 50-70 year agegroup, frequency ranging from 53.4% [18] to 68.1% [19]. The present study in which 148 patients (65.2%) were over 50 years of age is in agreement with those reports.…”
Section: Discussionsupporting
confidence: 94%
“…It is important to add that the mean age at onset of the disease in the patients in the present study (53.6± 12.1 years) is comparable with that of 60 ± 14 years reported by Larrodé-Pellicer et al [20] in your study in Zaragoza (Spain) and the study published by Cima et al [19] in Padova (Italy), in which mean age at onset was 64.8 ± 9.6 years.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies, however, were conducted using 5-year [14, 29, 30, 43, 47, 48] or 10-year intervals [16, 19, 20, 32, 39, 42, 44]. The most frequently used data collection method was medical records review (n = 16) [13, 19, 22, 3134, 3740, 42, 4446, 48], followed by ALS registries (n = 11) [14, 1618, 20, 21, 23, 27, 30, 35, 49], surveys (n = 5) [15, 17, 18, 21, 25, 2730, 43, 45, 47], and databases (n = 5) [24, 26, 36, 41, 47]. Most of the studies that used the medical records review approach were retrospective (81%); by contrast, most of the studies using ALS registries were prospective (70%).…”
Section: Resultsmentioning
confidence: 99%
“…Chiò et al [5] found that the incidence of ALS reaches its maximum from 60 to 75 years of age. However, in the Cima study, this ­maximum occurs from 65 to 74 years of age [16], while in several studies in Nova Scotia, Canada, from 70 to 79 years old [17]. …”
Section: Introductionmentioning
confidence: 99%